Analysis of Factors Affecting Non-performing Financing at Islamic Banks in Indonesia Using Error Correction Model Approach - Mohammad Dendi Abdul Nasir; Nunuk Khomariyah (Iqtishodia: Jurnal Ekonomi Syariah, 2021)
Banking plays a very important role in the country's economy. Financing of Islamic Banking certainly has non-performing financing. Worsening the NPF ratio means Syariah Bank has a high level of financial problems. This research aims to analyze the influence of internal factors (asset and financing deposit ratio) and external factors (inflation and exchange) against NPF to Syariah Bank in Indonesia. This research used a secondary data sourced from Indonesian Bank from January 2011 to June 2018. With using Error Correction Model (ECM) this research's result shows that in the short term only the FDR variable that has a significant impact on the NPF, while the asset variable, inflation, and exchange aren't influential. Then in the long term, asset variable and inflation influence significantly against Syariah Bank NPF, Whereas FDR variable and exchange aren't influential.